Evaluation of Soil Samples Preparation Techniques for Detecting Selenium by Using Atomic Fluorescence Spectroscopy-Based Detection - Lin Zhu; Zheng-he Hu; Xiu-long Chen; Surat Hongsibsong (Journal of Analytical Methods in Chemistry)
Selenium (Se) can cause poisoning in the human body, including dry, brittle, and easy-to-fall-off hair, white spots and longitudinal lines of nails, skin damage, nervous system abnormalities, and even death. In order to optimize the experimental process for the sensitive detection of Se in samples by atomic fluorescence spectrometry (AFS), an excellent experimental technique was selected to provide a reference for Se detection. In this study, the 3 soil sample preparation techniques were evaluated, i.e., the boiling water bath (BWB) method, electrothermal plate digestion (EPD) method, and microwave-assisted digestion (MAD) method. The Se content of soil samples were analyzed AFS and compared. The precision and accuracy of the calculation of soil standard were measured in parallel, and the recovery rate of the added standard was detected. The results show that the relative standard deviation (RSD) of BWB, EPD, and MAD was 2.16%, 3.78%, and 2.05%, respectively. The recoveries of BWB, EPD, and MAD ranged from 92.82%∼95.93%, 83.59%∼88.47%, to 96.92%∼97.86%, respectively. In short, compared with EPD, BWB and MAD can fully dissolve soil samples with ease, cost-effectiveness, reduced labor intensity, shorter experiment time, and high accuracy.